1987
DOI: 10.1128/jb.169.6.2893-2895.1987
|View full text |Cite
|
Sign up to set email alerts
|

Common evolutionary origin of the ilvGMEDA attenuation locus and tRNA(1Leu) in Escherichia coli

Abstract: Published sequences of transcripts from ilvGMEDA leader regions of several enteric bacteria were compared with published sequences of the tRNAs from Escherichia coli. The analyses revealed homology between the ilvGMEDA leader peptide-coding region and tRNALu in E. coli, Salmonella typhimurium, and Klebsiella aerogenes, whereas homology was not present in Serratia marcescens and Edwardsiella tarda.An attenuation mechanism has been proposed to account for multivalent control of transcription of the ilvGMEDA cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This metastatic cell line has several subtype specific characteristic changes in PI related enzymatic activity, namely in 3 -kinase Class I PI3K and 4 -phosphatase INPP4B. This cell line expresses a mutation in the Class I PI3K catalytic subunit which leads to an increase in activity linked to unregulated growth signaling [62][63][64][65][66][67]. This overexpression suggests an increase in the accumulation of PIP3 thought to be generated from PI(4,5)P2.…”
Section: Hormone Positive Breast Cancer Pi Trendsmentioning
confidence: 98%
“…This metastatic cell line has several subtype specific characteristic changes in PI related enzymatic activity, namely in 3 -kinase Class I PI3K and 4 -phosphatase INPP4B. This cell line expresses a mutation in the Class I PI3K catalytic subunit which leads to an increase in activity linked to unregulated growth signaling [62][63][64][65][66][67]. This overexpression suggests an increase in the accumulation of PIP3 thought to be generated from PI(4,5)P2.…”
Section: Hormone Positive Breast Cancer Pi Trendsmentioning
confidence: 98%
“…One of the negative regulators of AKT is the protein phosphatase and tensin homolog (PTEN), being a potential target of fucoidan. To examine this potential interaction, the PTEN expression of the affected cancer cell lines was retrieved from existing literature [99,100,101,102,103,104,105,106,107,108,109,110,111,112]. Almost all the cancer cell lines who were vulnerable for fucoidan, showed PTEN expression, except for PC-3 (bladder cancer) [101], MES-SA (uterine sarcoma) [102], and RL95-2 (endometrial cancer) [103].…”
Section: Summary Of Literaturementioning
confidence: 99%
“…Nevertheless the conservation of most of the segment homologous to the tRNA Trp gene (48 of 49 consecutive nucleotides) suggests some similar function at the two locations. Studies on several biosynthetic operons of enteric bacteria have suggested that the evolution of transcription-controlling sequences from tRNA genes may be of widespread occurrence (Ames et al 1983;Williamson and Jackson 1987).…”
Section: Discussionmentioning
confidence: 99%